Análise do potencial probiótico de Lactococcus lactis subsp. lactis NCDO 2118 por meio de genômica comparativa - Letícia de Castro Oliveira (2014)
Lactic Acid Bacteria (LAB) compose one of the most biotechnologically important group of bacteria. In this group, Lactococcus lactis is highly important for its use in the production of many fermented products and macromolecules and its application in health improvement it is a Generally Regarded As Safe (GRAS) species. Since this scenario, Lactococcus lactis subsp. lactis NCDO 2118 (herein, NCDO2118) stands out as a xylose fermenter and GABA (gamma-aminobutyric acid) producer strain isolated from frozen peas. GABA can contribute to smooth muscle relaxation and present a hypotensor activity. However, despite of those important characteristics, few is known about the mechanisms involved in probiotic effects of this strain. In this context, the genomic area can help elucidating unresolved issues. The comparative genomics has revolutionized the recent studies, through determining the genome plasticity between different species and/or strains, helping in driving experimental studies. In this work, we have sequenced and manually curated the genome of NCDO2118. Besides, we have compared the genome of NCDO2118 with those of 5 additional L. lactis subsp. lactis, 6 Lactococcus lactis subsp. cremoris and 2 Lactococcus garvieae strains. We used the software Gegenees, Mauve and BRIG to perform phylogenomics, gene synteny and circular genome comparisons between the above mentioned species. Additionally, we have used GIPSy and Phast to predict genomic islands (GEIs) and phages, respectively. We have predicted secreted proteins using SurfG+ tool. In phylogenomics analyses, a high similarity was observed between NCDO 2118 and L. lactis subsp. lactis KF147 (herein, KF147), both isolated from plants. Besides, the gene synteny analyses have clearly shown a highly conserved gene order between both strains. We have also predicted 15 putative GEIs, where four are metabolic islands (MIs) and seven are symbiotic islands (SIs). The four MIs are commonly shared by all strains analyzed here, whereas two of the SIs are only shared by NCDO2218 and KF147. Finally, we have identified five phage regions and 3 bacteriocins, one of each class(classes I, II and III), along with 98 bacteriocin-related genes, which may support the regulation and secretion of the bacteriocins. The predicted secreted proteins of NCDO 2118 were compared with Lactococcus lactis subsp. lactis IL1403 proteins, considered recently as a non-probiotic strain. Therefore, 34 proteins were present exclusively in NCDO 2118 and some of them can have relationship with its probiotic ability. Altogether, the high degree of similarity between all strains point that the SIs commonly shared by both NCDO2118 and KF147 were responsible for the close relationship in phylogenomic analyses and also for the adaptation of those strains to plants. The MIs, on the other hand, are highly conserved between all strains, which is a expected feature given the use of those strains in metabolic processes in industry. Finally, the three classes of bacteriocins may have an important role against invasion of competing strains or influencing the host immune system, which may be involved in the probiotic characteristic of this strain.